The effect of waiting time on ovarian cancer survival in oncology centres, Addis Ababa, Ethiopia: a retrospective cohort study - Abrham Tesfaye Habteyes; Jembere Tesfaye Deressa; Roza Teshome Kassa (BMC Women's Health)
Abstract Background Ovarian cancer is a leading cause of mortality worldwide. The third most prevalent gynecological cancer globally, following cervical and uterine cancer, and the third leading cause of cancer-related mortality among women in Sub-Saharan Africa, including Ethiopia. The time ovarian cancer patients have to wait between diagnosis and initiation of treatment are the indicators of quality in cancer care and influence patient outcomes. Despite extensive studies in the field, little is known about the strength of the association between ovarian cancer survival and waiting time. So, the main purpose of this study is to assess the effect of waiting time on ovarian cancer survival in oncology centers in Addis Ababa, Ethiopia. Methods A facility-based retrospective cohort study was conducted with a total of 561 study participants included. The main outcome of interest for this study was death due to ovarian cancer. The authors compared the ovarian cancer patients with waiting times ≤ 10 weeks and waiting times > 10 weeks for overall survival rate using the log rank test. The incidence density rate of mortality was calculated for each group variable. The effect of waiting time on ovarian cancer mortality was estimated using the Cox proportional hazards model at the 5% level of significance. Results The incidence density rate of mortality among ovarian cancer patients for waiting time ≤ 10 weeks was found to be 10.85 (95%CI, 9.10-12.98) per 1,000 person years observation, while for waiting time > 10 weeks the mortality rate was found to be 18.05 (95%CI, 15.33–21.23) per 1,000 person years observation. In the Cox regression analysis after full adjustments for confounder variables, the mortality event risk was 36% higher among waiting time > 10 weeks women (AHR = 1.36; 95%CI = 1.05–1.75) as compared to waiting time ≤ 10 weeks. Conclusions We have found that the incidence density rate of mortality among ovarian cancer patients was significantly higher in waiting time > 10 weeks groups. Therefore, future policy and clinician programmers should consider the impact of waiting time from diagnosis until to get the first treatment more carefully.